Faktor Pembentukan Akhlak: Internal, Eksternal dan Spiritual yang Berperan - Syifa, Uzlifatu; Raihanuddin, Muhamad; Ajma’in, Maftuh (Lembaga Yasin AlSys, 2025)
Moral formation is a process that is influenced by various aspects, including technology, environment, education, and the role of family and society. The development of technology, such as television and social media, has a huge impact on the mindset and behavior of individuals, especially children. While technology has its benefits in disseminating information and entertainment, negative content such as violence and pornography can damage morale and form habits that go against moral values. In addition to technology, the social environment also plays an important role in shaping individual character. Children tend to mimic the behavior they see from their families, teachers, religious leaders and community leaders. Therefore, moral education is not only the responsibility of educational institutions, but also requires the active role of parents and society in setting a good example. This article discusses the various factors that influence moral formation and emphasizes the importance of guidance and supervision in shaping moral character. With the right approach from various parties, it is hoped that the younger generation can grow into moral individuals who are able to face the challenges of the times wisely.